Association between Escherichia coli and Salmonella spp. food safety criteria in live bivalve molluscs from wholesale and retail markets - Mudadu, A. G.; Spanu, C.; Pantoja, J. C.F. [UNESP]; Dos Santos, M. C. [UNESP]; De Oliveira, C. D. [UNESP]; Salza, S.; Piras, G.; Uda, M. T.; Virgilio, S.; Giagnoni, L.; Pereira, J. G. [UNESP]; Tedde, T. (Elsevier, 2022)
This study presents epidemiological data on the prevalence of Salmonella spp. and E. coli in bivalve molluscs marketed in Sardinia (Italy). E. coli enumeration and Salmonella spp. occurrence at batch level were used to verify the association between microbiological food safety criteria in place in the European Community. From 2017 to 2020 bivalve molluscs samples including 2115 mussels (Mytilus galloprovincialis), 150 oysters (Crassostrea gigas) and 65 clams (Ruditapes decussatus) were collected at wholesale market and retail stores from 8 provinces of Sardinia. All samples were collected during official control activities and analyzed for the enumeration of E. coli according to the Most Probable Number (MPN) method (ISO 16649-3) and for the detection of Salmonella spp. according to the reference method ISO 6579-1 (ISO, 2017). Evaluation of E. coli and Salmonella spp. contamination was conducted at sample unit level while satisfaction of microbiological criteria was evaluated at batch level (each batch was composed of 5 bivalve molluscs sample units). Logistic regression was used to estimate the chances of observing an E. coli unsatisfactory batch as a function of year of collection (2017, 2018, 2019 and 2020), molluscs species (mussels, oysters, and clams), season (winter, fall, spring, and summer), and type of market (wholesale or retail). The Chi-square test was used investigate the association between the occurrence of E. coli and Salmonella spp. in the study sample. Overall, E. coli was <230 MPN/100 g in 97.6% of the samples while Salmonella spp. was detected in 0.6% of the samples. At batch level, unsatisfactory results for E. coli and Salmonella spp. were observed in 2.6% and 1.7% of the samples, respectively. Instances of values above the limit were all observed in mussel's samples. The chances of E. coli unsatisfactory results were not different among the years of collection, bivalve species, season, or market type. No significant association was observed between E. coli and Salmonella spp. at both sample unit and batch levels, revealing a poor association between the two criteria in the final product. Overall, the edible bivalve molluscs marketed in Sardinia demonstrated a high microbiological quality and compliance with European Union criteria.
Keywords: Food safety; Official control; Shellfish